Statement by the Managing Director on the Work Program of the Executive Board Executive Board Meeting : December 10, 2020. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2021)
As the COVID-19 crisis continues to unfold, uncertainty remains exceptionally high. The Fund has provided extraordinary financial support as well as timely analysis and policy advice during the first phase of the crisis, but additional efforts are needed to help members secure a durable exit, minimize long-term scarring, and build a more sustainable and resilient economy. Against this backdrop, and in line with the strategic directions laid out in the Fall 2020 Global Policy Agenda and the International Monetary and Financial Committee (IMFC) Communique, this Work Program puts forward a prioritized Board agenda for December 2020 to June 2021, focused on activities of most critical importance to our members.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Health Behavior; Monetary Policy; Political Economy